The effect of aerobic on the Hemocystein and respiratory selective factors Levels - Hossien zade Mehdi, Niknam Far Ali, Hatami Hojat, Rangraz Ebrahim, (Opción, 2019)
The purpose of the present study is the examination of the effect of aerobic exercises on the level of Hemocystein and on the respiratory selective factors of inactive middle-aged men suffering from the type two of diabetes via the covariance analysis in statistical tests. The findings showed that there are some significant differences between the two groups in respiratory factors but there are not any significant differences in the amount of Hemocystein. In conclusion, people suffering from the second type of diabetes can be recommended to use the aerobic exercises as the effective.